Liturgical laboratories? - Pennington, Robert (Journal of Religious Education, 2014)
The primary claim of my research is that students learn about religions most effectively through methods that are experience-based, context-situated, and practice-centric. However, my claim is not new. Forms of immersion learning, which are always experience-context-practice-centric, have been around for quite some time. Numerous scholars call attention to the importance of experience-based, context-situated, and practice-centric forms of immersion learning. For example, see Place-Based Education in the Global Age (Gruenewald and Smith 2008); Knowing and Doing: Learning Through Experience (Hutchings and Wutzdorff 1988); Estey, Ken, "The "Place" of Place-Based Pedagogy in Teaching Religion: Brooklyn and Its Religions" (Etsey 2014); Cowden, Stephen; and Singh, Gurnam, Acts of Knowing: Critical Pedagogy in, Against and Beyond the University (Cowden and Singh 2013); Knowledge, Pedagogy, and Postmulticulturalism: Shifting the Locus of Learning in Urban Teacher Education (Wilgus 2013); Yuskaev, Timur, "Staying Put: Local Context as Classroom for Multifaith Education" (Yuskaey 2013); "Experiential Learning: Theory and Challenges" (Hedin 2010); "Becoming Pilgrims: Engaging Theory Through Practice in the Introductory World Religions Course" (Hill 2004).